The impact of age in the generation of satisfaction and WOM in mobile shopping. (March 2015) - San-Martín, Sonia; Prodanova, Jana; Jiménez, Nadia
Abstract: M-commerce in Spain is in its early stages and firms will be interested in knowing the factors that affect recommendation (word of mouth – WOM) of an m-purchase. In this research, we will study perceived entertainment and group influence (subjective norms) in purchase as determinants of satisfaction with m-shopping and WOM. There is some research studying WOM in an m-commerce context, but no study has considered the role of the age in the Spanish case. To that aim, we will make a distinction here between young adults (individuals under 25 years old) and adults (individuals over 25 years old) that already have an m-shopping experience, presenting factors that most influence WOM about m-shopping. With information obtained from 447 Spanish m-buyers, we have found that the perceived entertainment has higher importance for young adults and the subjective norms are crucial for adults. Satisfaction is a relevant determinant of WOM in both m-buyers groups. Results indicate interesting implications for the companies and the literature, as well. Highlights: Entertainment and subjective norms enhance satisfaction with m-shopping. Entertainment and satisfaction positively influence WOM about m-shopping. Entertainment has higher importance for young adults. Subjective norms are crucial for adults.